Shoreline and coastline of claromecó, Buenos Aires Province - Kokot, R.R. (2011)
The coastline position in Claromecó, Buenos Aires province was determined, featuring character elements identified in relation to the position of the shoreline. In comparison on the determination of coastline and shoreline, it appears that the first results of the geomorphologic interpretation, while the position of the shoreline is subject to a number of uncertainties if there are no long-term measurements. The nomenclature for the coastal areas is not always clear, hampering the interpretation of the processes occurring in the coast and shore. The correct identification is important technical, scientific and legal. Current legislation states that the boundary between public and private territory corresponds to the shoreline. The use of plant species in the determination of the coastline and shoreline, by itself is not determinative if not accompanied by the geomorphologic reconnaissance of the area. The exact determination of shoreline and coastline is essential in the implementation of geological surveys of major importance for the proper planning and development of the coastal area. In the task of delimitation of the coastal area beach ridges were found; one located about 5 m a.s.l has an age of 4,370 years BP.